Model Perilaku Partisipasi Warga di Bank Sampah (Studi Kasus di Bantul, DIY) - Reni Dwi Astuti; Utaminingsih Linarti (Jurnal Optimasi Sistem Industri, 2020)
The increasing volume of waste in Bantul Regency is a problem that must be solved. One of the things that the Regency Government does is by promoting waste banks. From the existing waste banks, citizen participation is still low, so it is not significant enough to reduce the volume of waste disposed of at the Piyungan landfill. One of the factors identified is the low interest of residents to join the waste bank. For this reason, a study of citizens' behavior is needed so that they join the waste bank with a theory of planned behavior coupled with knowledge of how and what and knowledge of consequences factors. Data collection was carried out by distributing questionnaires to members of the garbage bank. The number of respondents was 1265 from 29 waste banks spread throughout Bantul Regency. The method of data analysis uses linear regression. Research shows that attitudes, perceived behavioral control, knowledge of how and what, and knowledge of consequences have positive and significant effects, both simultaneously and partially, on the intention of residents to join the waste bank. Intention is also a significant positive and significant effect on behavior.